Improved intervention of atherosclerosis and cardiac hypertrophy through biodegradable polymer-encapsulated delivery of glycosphingolipid inhibitor. (September 2015) - Mishra, S.; Bedja, D.; Amuzie, C.; Foss, C.A.; Pomper, M.G.; Bhattacharya, R.; Yarema, K.J.; Chatterjee, S.
Abstract: D-Threo-1-phenyl-2-decanoylamino-3-morpholino-1-propanol (D-PDMP), a glycosphingolipid synthesis inhibitor, holds promise for the treatment of atherosclerosis and cardiac hypertrophy but rapid in vivo clearance has severely hindered translation to the clinic. To overcome this impediment, we used a materials-based delivery strategy wherein D-PDMP was encapsulated within a biodegradable polymer composed of poly ethylene glycol (PEG) and sebacic acid (SA). PEG-SA was formulated into nanoparticles that were doped with 125 I-labeled PEG to allow in vivo bio-distribution and release kinetics of D-PDMP to be determined by using γ-scintigraphy and subsequently, by mass spectrometry. Polymer-encapsulation increased the residence time of D-PDMP in the body of a treated mouse from less than one hour to at least four hours (and up to 48 h or longer). This substantially increased in vivo longevity provided by polymer encapsulation resulted in an order of magnitude gain in efficacy for interfering with atherosclerosis and cardiac hypertrophy in apoE−/− mice fed a high fat and high cholesterol (HFHC) diet. These results establish that D-PDMP encapsulated in a biodegradable polymer provides a superior mode of delivery compared to unconjugated D-PDMP by way of increased gastrointestinal absorption and increased residence time thus providing this otherwise rapidly cleared compound with therapeutic relevance in interfering with atherosclerosis, cardiac hypertrophy, and probably other diseases associated with the deleterious effects of abnormally high glycosphingolipid biosynthesis or deficient catabolism.